DETERMINANTS OF GOING CONCERN AUDIT OPINION ACCEPTANCE ON FINANCIAL SERVICE COMPANIES IN THE IDX - Hamsyi, Nur Fitriana; Yosevin (Fair Value: Jurnal Ilmiah Akuntansi dan Keuangan, 2022)
Going concern describes the company's ability to maintain its business continuity in the future. The auditor can issue a going concern audit opinion if the company's condition is doubtful in its business continuity. This study analyzes the effect of the previous year's audit opinion, debt default, company size, company growth on the acceptance of going concern audit opinions on financial services companies listed on the Indonesia Stock Exchange. A total of 60 companies were obtained using purposive sampling within three years so that the data produced were 180 observations. Based on logistic regression with SPSS 24 analysis tool, it is proven that the previous year's audit opinion positively affects the acceptance of the business continuity audit opinion. While the defaulted debt, company size, company growth did not affect the acceptance of going concern audit opinion.